Estudo português de Hipercolesterolaemia Familiar - Bourbon, Mafalda (2019)
Main Aim: To identify the cause of the dyslipidaemia in patients with a clinical phenotype of Familial Hypercholesterolaemia (FH). Secondary aims: To implement the genetic diagnosis of FH; To perform an epidemiological study of FH; To study the pathophysiology of premature CHD in FH patients.